New Foods for Healing: Capture The Powerful Cures Of More Than 100 Common Foods - Selene Yeager
A comprehensive guide to recent research and developments in the use of food to ease and even heal ailments such as arthritis, heart disease, skin damage and cancer also includes more than one hundred recipes designed for both taste and curative power.